Modified Combined Fascia Sheath and Levator Muscle Complex Suspension With Müller Muscle Preservation on Treating Severe Congenital Ptosis. Issue 1 (January 2019) - Xing, Yue; Wang, Xi; Cao, Yuan; Ding, Xia; Lin, Ming; Li, Jin; Fan, Xianqun
Abstract : Background: This study aims to evaluate the effect of a modified approach on severe congenital ptosis treatment. Methods: Through anterior approach, Müller muscle was preserved, meanwhile the upper tarsus was suspended to combined fascia sheath (CFS) and levator muscle (LM) complex. The main outcome measures included marginal reflex distance1 (MRD1), palpebral fissure height (PFH), MRD1 regression, MRD1 improvement, and patient self-satisfaction. Results: There were 70 patients (90 eyelids) with severe congenital ptosis received treatment of modified operation, including 20 bilateral and 50 unilateral ptosis. The average LF was 2.53 ± 1.06 mm. The preoperative MRD1 and PFH was −0.06 ± 0.76 mm and 4.25 ± 0.85 mm, respectively. The follow-up was at least 6 months with average of 12.67 ± 4.92 months. The immediate postoperative MRD1 and PFH average was 4.52 ± 0.39 mm and 9.24 ± 0.26, respectively. The last follow-up MRD1 and PFH average was 2.43 ± 0.57 mm and 7.16 ± 0.69 mm, respectively, which was improved significantly ( P < 0.01). There were variety degrees of MRD1 regression especially in the first month after operation, and the last follow-up MRD1 regression was 2.09 ± 0.67 mm. The lagophthalmos was obvious immediately after operation and regularly released after 6 months. Objective curative effect assessment showed 78 (86.7%) satisfactory eyes, 4 (4.4%) improved eyes, and 8 (8.9%) noneffective eyes. Two noneffective eyes required reoperation of frontalis suspension. Self-satisfaction rate was 93.3%. Parameters analysis showed that LF had positive correlation with last follow-up MRD1 and negative correlation with MRD1 improvement ( P < 0.01). Five eyes had levator shorten history, which was associated remarkably with CFS + LM curative effect ( P < 0.01). Mean swelling time was 0.53 ± 0.41 months, and no complications were observed until the last visit. Conclusions: This modified method gives powerful correction and vivid eyelid contour, featured with simple surgical procedures, few complications, and satisfactory effect, which is worth to wide application. Abstract : Supplemental digital content is available in the text.